An analysis of metadata reporting in freshwater environmental DNA research calls for the development of best practice guidelines. Issue 3 (19th March 2020) - Nicholson, Andrew; McIsaac, Daniel; MacDonald, Caitlin; Gec, Peter; Mason, B. Eric; Rein, William; Wrobel, Jordan; de Boer, Mats; Milián‐García, Yoamel; Hanner, Robert H.
Abstract: As environmental DNA (eDNA) becomes more widely used in research, it becomes increasingly important to have a standard set of reporting guidelines for metadata. The unique properties of eDNA combined with the physical characteristics of the surrounding environment produce highly varied sampling conditions which can influence how an organism is detected. There are also various ways of quantifying and identifying species using eDNA, from sampling and filtering methods to extraction and genetic analysis. It is important to report sufficient metadata to account for this variability and allow for replication of the study. We conducted a systematic review of 160 eDNA studies to determine which data are reported and to assess whether these studies can be replicated. Focusing solely on freshwater studies, we developed a rubric to evaluate each study on 53 criteria based on previous analyses of eDNA research. We found a trend in the data suggesting better reporting at a broad scale, and decreased reporting as categories become more specific. Many of the metrics found to be insufficiently reported are essential to replicability. Our goal is to identify gaps in metadata reporting and develop a framework for developing standard reporting guidelines for eDNA studies. Abstract : A metadata review of current eDNA literature to determine the reporting gaps. Standardization of metadata reporting will improve the replicability and reliability of future eDNA studies.